Impact of radicalism and terrorism through social media among youth in the Film The Lone Wolf Next Door - Muchammad Zaenal Al Ansory; Anggar Erdhina Adi (International Journal of Visual and Performing Arts, 2024)
This research delves into the detrimental impacts of social media utilization among young individuals as a conduit for radicalism and terrorism propagation. Focusing on "The Lone Wolf Next Door," the study illustrates the journey of Alif Himawan, a high school student entrapped in jihad ideology disseminated through social platforms. Alif's trajectory escalates as he acquires bomb-making skills, culminating in church suicide bombings. The research aims to portray societal realities through cinematic portrayal, drawing from the 2016 Medan tragedy involving Ivan Armadi Hasugian as inspiration. By analyzing the filmmaking process of "The Lone Wolf Next Door," the study endeavors to shed light on pertinent issues. Employing a realism approach, the film is not only scrutinized as a cinematic entity but also serves as a discourse platform regarding realism's intersection with radicalism and terrorism. Methodologically, descriptive qualitative analysis facilitates reality reconstruction, utilizing primary and secondary data from literature reviews, observations, and interviews. The findings highlight the pivotal role of film in broadening deradicalization efforts targeting the youth demographic. In conclusion, "The Lone Wolf Next Door" not only serves as a cinematic narrative but also contributes to the discourse on countering radicalism, emphasizing the significance of media in societal intervention strategies.